Geopark Silokek Sijunjung Menuju UNESCO Global Geopark - Desi Widia Kusuma (Jurnal Pembangunan Nagari, 2019)
Silokek Geopark is located in Sijunjung Regency with an area of ​​± 1300 km2. Silokek Geopark has been designated as the National Geopark on 30 November 2018 with 25 geodiversity sites, 12 biodiversity sites and 17 cultural diversity sites. After being designated as the National Geopark, the next hope is to be designated as the UNESCO Global Geopark. Based on this, a study was conducted which aimed to analyze the condition of the Geopark Silokek based on UNESCO Global Geopark criteria and to find out the challenges in the development of Silopek Geopark. The study was conducted in May-August 2018 in Sumpur Kudus District and Sijunjung District. Primary data is obtained from field observations and interviews with relevant agencies, while secondary data is obtained based on searches of technical documents and journals. From the results of the study it is known that several UNESCO criteria that need to be improved and disemployed are the management of Geopark Silokek, aspects of economic development and aspects of education. This improvement can be done by revising the structure of the Silokek Geopark Management Agency, building geotrack lines and supporting facilities, increasing community empowerment and overcoming environmental problems on the Batang Kuantan River.